2016
DOI: 10.1039/c5cc08307a
|View full text |Cite
|
Sign up to set email alerts
|

From insertion to multicomponent coupling: temperature dependent reactions of arynes with aliphatic alcohols

Abstract: The temperature dependent selectivity switch in the reaction of arynes with aliphatic alcohols in THF has been reported. At -20 °C, arynes smoothly insert into the O-H bond of alcohols to form alkyl aryl ethers. Interestingly, at 60 °C, a highly selective multicomponent coupling occurs with the solvent THF acting as the nucleophilic trigger affording (4-(alkoxy)butoxy)arenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 42 publications
1
31
0
1
Order By: Relevance
“…Biju reported that the reaction of arynes with alcohols in THF as a solvent preferentially generates three-component assembly product 60 over the alcohol insertion product. 76 Yoshida reported that 59 readily reacts with aryl or alkynyl bromides followed by ring opening to generate o-bromoaryl ether 61. 29 Cyclic thioethers react with arynes in a similar manner as cyclic ethers (Scheme 22).…”
Section: Trapping With Ethers and Thioethersmentioning
confidence: 99%
“…Biju reported that the reaction of arynes with alcohols in THF as a solvent preferentially generates three-component assembly product 60 over the alcohol insertion product. 76 Yoshida reported that 59 readily reacts with aryl or alkynyl bromides followed by ring opening to generate o-bromoaryl ether 61. 29 Cyclic thioethers react with arynes in a similar manner as cyclic ethers (Scheme 22).…”
Section: Trapping With Ethers and Thioethersmentioning
confidence: 99%
“…1‐Methoxy‐4‐(phenoxymethyl)benzene ( 3 d ) . White solid (35.7 mg, 84 %, Procedure A ), a mixture of petroleum ether/ ethyl acetate=40/ 1 (v/ v) as eluents for column chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…More generally, "there are limited examples of O-arylation transformations" [6] using arynes (scheme 1, B), overall restricted to few hydroxyl and carboxylgroup arylation protocols since 2004. [30][31][32] Despite the many studies scrutinizing the reactivity of diverse arynophiles, the ability of phosphates to engage in reactions with arynes is absent from the literature. This is remarkable, as the urgent need to access probes for interrogation of phosphate functions, e.g.…”
Section: Introductionmentioning
confidence: 99%